Decomposition dynamics of sugarcane straw in the central-southern Brazil - Pimentel, Laisa Gouveia (2017)
The adoption of mechanical unburned sugarcane harvesting increases the quantity of straw left on the soil. This material has a high potential for 2G ethanol and bioelectricity production. Although the straw maintenance has an essential role in the soil properties and crop performance. The straw decomposition is a key process to investigate and to inform the correct removal management decisions. Diverse factors affect the decomposition rate, such as: quality and quantity of straw; edaphoclimatic conditions; and management practices. Therefore, we conducted a field study at two sites within central-southern Brazil, the largest sugarcane-producing region in the world, encompassing two harvesting seasons (rainy and dry) over two years to evaluate the sugarcane straw decomposition dynamics under different removal rates. The main hypothesis is that the high removal unbalances the soil environment and reduce de C supply for the microorganisms, decreasing the microbial activity and consequently the straw decomposition rate. The straw removal management affected the decomposition rate, which the lowest decomposition was associated with high removal. The C and N loss was two- and threefold greater in the second year than in the first year of experimentation, respectively. Overall, the straw cellulose decreased by 13%, the hemicellulose 7%, and the lignin proportionally enriched by 92% after two years. Throughout the decomposition process, the straw chemical changes were detected using the traditional method, wet chemical extractions, and using the spectroscopy technique, Diffuse Reflectance Infrared Fourier Transform DRIFT. In this sense, in order to trace straw cellulose and hemicellulose changes we suggested the use of 896, 987, 1173, and 1447 cm-1 peaks, whereas to trace lignin changes, the absorbance at 1510 cm-1 seems to be an efficient predictor. The soil bacterial community was most affected by the time of decomposition. The straw quality explained 23.2% of the total bacterial variation, in which hemicellulose accounting for 17.2% of this variation. Moreover, the bacterial structure was subtle affected by the sugarcane straw removal. Overall, our study showed that the straw removal for 2G ethanol and bioelectricity production affect the straw decomposition dynamics in commercial sugarcane areas in Brazil. The time was the main regulator of changes in straw chemical contents and in the soil bacterial structure. The use of crop residues for energy purposes is one of the principal alternatives to increase bioenergy production in the next few years. However, the sugarcane straw removal should be done with prudence, since the straw removal rate affected the straw decomposition dynamics and consequently it should affect the nutrient recycling and C cycle.